The inspiratory muscle training in elite rowers - Klusiewicz, A.; Borkowski, L.; Zdanowicz, R.; Boros, P.; Wesolowski, S. (The Journal of Sports Medicine and Physical Fitness, 2008)
Aim. The aim of the investigation was to assess the effects of the resistive inspiratory muscle training (IMT) in elite male rowers. Methods. Fifteen senior rowers were assayed for the maximal inspiratory mouth pressure (PImax) and maximal oxygen uptake (V.O2max), and then randomized into two groups: the control and the experimental group. The latter athletes, in addition to basic training, were subjected to the 11-week IMT consisting of a series of 30 inspiratory efforts performed twice a day. Athletes from the control group did only the basic training. Results. No significant relations were detected between the initial values of PImax and the V.O2max value. After 6 weeks of IMT the PImax values increased by 20±10% (P<0.05), whereas the final improvement (after 11 weeks of IMT) equaled to 34±19% (P<0.05). In the control group, the final increase equaled to 4±9% and was statistically insignificant. Compared to the values obtained at the end of IMT, 14 weeks after cessation of the training PImax insignificantly decreased in the experimental group by 10±9%, but the measured values were still significantly higher than before the commencement of IMT. Conclusion. The data obtained corroborate the observations that in well-trained athletes the introduction of the principle of incremental inspiratory resistance allows to improve methodically the inspiratory muscles' strength. Once the essential period of IMT has been completed, the training volume should be reduced in order to secure the attained level of the inspiratory muscles' strength.